Relación entre las importaciones y los ingresos recaudados por tributos aduaneros en el departamento de Loreto periodo 2018-2023 - Carbajal Zambrano, Juan (2025)
This research analyzes the relationship between imports and customs tax revenues in the department of Loreto, Peru, during the period 2018-2023. Using a quantitative approach and a non-experimental design, a Spearman correlation analysis was applied to evaluate the variables under study. The results show a positive and moderate relationship between the volume of imports and customs tax revenues, with a correlation coefficient of Rho = 0.4408, indicating that although imports and customs taxes are linked, other factors also affect tax collection. Furthermore, it was observed that imports in Loreto exhibit a growing, yet irregular, trend, suggesting that fluctuations in demand and external trade policies significantly impact this relationship. Revenue from internal taxes, while also showing a positive trend, is not as closely related to imports, highlighting the influence of other economic and fiscal factors on its evolution. This research contributes to understanding the fiscal and commercial dynamics in Loreto, emphasizing the importance of efficient fiscal and trade policies to maximize tax revenues and promote formal and sustainable foreign trade.